2006
DOI: 10.1534/genetics.106.058099
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for Locomotor Behavior inDrosophila melanogaster

Abstract: Locomotion is an integral component of most animal behaviors and many human diseases and disorders are associated with locomotor deficits, but little is known about the genetic basis of natural variation in locomotor behavior. Locomotion is a complex trait, with variation attributable to the joint segregation of multiple interacting quantitative trait loci (QTL), with effects that are sensitive to the environment. We assessed variation in a component of locomotor behavior (locomotor reactivity) in a population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 82 publications
4
67
1
Order By: Relevance
“…Only three of these genes (Beadex, Sema-5c, and neur) had previously been documented to affect locomotion (19)(20)(21). Many of these candidate genes affect nervous system development and function, as well as other aspects of development, the cell cycle, and oogenesis and spermatogenesis, consistent with previous observations that genes affecting startle-induced locomotion are highly pleiotropic (5,11,12).…”
supporting
confidence: 84%
See 3 more Smart Citations
“…Only three of these genes (Beadex, Sema-5c, and neur) had previously been documented to affect locomotion (19)(20)(21). Many of these candidate genes affect nervous system development and function, as well as other aspects of development, the cell cycle, and oogenesis and spermatogenesis, consistent with previous observations that genes affecting startle-induced locomotion are highly pleiotropic (5,11,12).…”
supporting
confidence: 84%
“…The flies were subjected to a gentle mechanical disturbance by tapping the vial lightly, then placing it horizontally under a fluorescent lamp. Locomotor behavior was quantified as the number of seconds each fly was active during an observation period immediately following the disturbance (5,11). The observation period lasted 30 s for the homozygous mutation screen and 45 s for the epistasis analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in all studies reported to date, both common and rare QTNs have been associated with quantitative traits and occur in presumed regulatory regions, as well as nonsynonymous polymorphisms in coding regions (Mackay and Langley 1990;Long et al 2000;Robin et al 2002;Palsson and Gibson 2004;Jordan et al 2006). Although the total number of studies is small, there is a tendency for less common polymorphisms associated with quantitative traits to Effect sizes (expressed as percentage of total variation explained) for six categories of phenotype.…”
Section: How Much Does Genetic Architecture Vary Between Phenotypes?mentioning
confidence: 99%